2022
DOI: 10.3389/fphar.2022.952562
|View full text |Cite
|
Sign up to set email alerts
|

Nation-Wide Survey Assessing the Knowledge and Attitudes of Romanian Pharmacists Concerning Pharmacogenetics

Abstract: Background: Pharmacogenetics (PGx) is an important component of personalized medicine that has the potential to improve medicines’ effectiveness and safety. However, despite progress in technology and availability, PGx testing application into patient-care in Eastern Europe countries, has been slow.Objectives: Our aim was to describe knowledge and attitudes of Romanian pharmacists concerning PGx, and identify potential factors limiting PGx implementation.Method: An anonymous, web-based questionnaire was distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Final-year students shared the lowest level of satisfaction regarding their studies which may be attributed, inter alia, to their internships at community and hospital pharmacies. These results are consistent with other studies in which 60.3% of individuals believed that their university education was insufficient and only a third of them supposed that lectures were comprehensive and clear [8,Table 7 Standardised direct, indirect and total effects for the SEM model 15]. This descending trend highlighted the insufficiency of PGx-related material in latent modules and the students' demand for a more tailored educational scheme that focuses more on learner's skills, needs and wants.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Final-year students shared the lowest level of satisfaction regarding their studies which may be attributed, inter alia, to their internships at community and hospital pharmacies. These results are consistent with other studies in which 60.3% of individuals believed that their university education was insufficient and only a third of them supposed that lectures were comprehensive and clear [8,Table 7 Standardised direct, indirect and total effects for the SEM model 15]. This descending trend highlighted the insufficiency of PGx-related material in latent modules and the students' demand for a more tailored educational scheme that focuses more on learner's skills, needs and wants.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, Mahmutovic et al, 2018 mentioned that 60% of the students asked would like to continue their studies in the field, Schwartz et al 2017 demonstrated that 97% of the hospital pharmacists expressed interest in continuing their training, while in Indonesia, 94.2% of pharmacists were interested in future education [42] along with Jordan where a 75% of pharmacists expressed their will to participate in postgraduate training activities or seminars [14,42,44,47]. Based on Pop et al, 2022, and Filiptsova et al, 2015, new generation of pharmacists were more progressive and willing to implement innovative technologies and interventions in their clinical practice with the objective to improve patient experience and provide them with better quality of services [8,48]. To achieve it, it is fundamental to receive official training and accreditation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably because experiences and lessons learnt during their study years were heightened and better understood during their early career years. Similar inferences were made in a study conducted in Romania by Pop et al 2022 . A recent survey of the Southeast Asian Pharmacogenomics Research Network (SEAPHARM) showed that, in Malaysia, contents for basic genetic and pharmacogenomics are integrated within the national pharmacy curriculum.…”
Section: Discussionsupporting
confidence: 87%